LEARNERS’ SATISFACTION LEVEL WITH ONLINE STUDENT PORTAL AS A SUPPORT SYSTEM IN AN OPEN AND DISTANCE eLEARNING ENVIRONMENT (ODeL) - SECRETO, Percia V.; PAMULAKLAKIN, Rhodora L. (The Turkish online journal of distance education TOJDE, 2015)
Learner support in an open, distance and online learning is defined as "all activities and elements in education that respond to a known learner or group of learners, and which are designed to assist in the cognitive, affective, and systemic realms of the learning process" (Brindley, et. al, 2004). Teaching and tutoring, advising and counseling, and information and administration are the main institutional systems involved in learner support. The UP Open University functions under an open and distance e-learning (ODeL) framework of distance education where most of its academic and non-academic processes are done through the Internet. It has developed an online Academic Information Management System (AIMS) which serves as the gateway to the University's academic operations. The Online Student Portal (OSP) is the component of the system for the students. OSP serves such functionalities as online registration, viewing of grades, request for their records, payment of fees, and information hub. The study analyzed the learners' satisfaction with the portal's functionality, efficiency, appearance, ease of use, and security. An online survey was conducted of continuing undergraduate and graduate students (n = 147) who were admitted prior to the implementation of the portal and thus had experienced both the manual and online processes. The survey was conducted from September 26 to October 3, 2013. In general, about 85 percent of those who participated in the survey were either very satisfied or satisfied with their overall experience of the portal. Ninety percent of the total participants found the portal cost-effective and informative. Overall, the participants identified the portal as a convenient and effective venue for getting accurate and immediate information about their performance, school activities, academic schedules, and other information relevant to their learning transactions. These features had made the portal an important student support tool that may enhance the learning experience of online learners.